MODERN TECHNOLOGIES AND APPROACHES TO APOPTOSIS STUDIES IN EXPERIMENTAL BIOLOGY - I. V. Kudriavtsev; A. S. Golovkin; A. V. Zurochka; S. V. Khaidukov (Медицинская иммунология, 2014)
Abstract. This review is focused on analysis of currently used flow cytometric methods designed foridentifying apoptotic cells in various invertebrate and vertebrate species. Apoptosis can be characterized by stage-specific morphological and biochemical changes that are typical to all kinds of eukaryotic cells. In this article, we consider different techniques of apoptosis detection based on assessment of cellular morphology and plasma membrane alterations, activation of intracellular enzymes and components of a caspase cascade, as well as DNA fragmentation and failure of mitochondrial transmembrane potential, as assessed in various animal groups. Apoptosis recognized as a key mechanism aiming at maintenance of cellular homeostasis in multicellular organisms, and such investigations represent a necessary component of fundamental and applied studies in diverse fields of experimental biology and immunology. A broad spectrum of apoptosis markers isused, and the preference is given to optimal approaches, as determined by experimental tasks, and technical opportunities of the laboratory.